The Influence of High Intensity Interval Training (HIIT) on VO2Max Endurance in Extracurricular Basketball Participant at SMA - Ridwandhani, Rifki Ahmad; Iskandar, Dedi (Yayasan Insan Mulia Bima, 2025)
VO2Max is an indicator of aerobic fitness that greatly determines performance in high-intensity sports such as basketball. This study seeks to analyze the effect of implementing High Intensity Interval Training (HIIT) on increasing VO2Max endurance in extracurricular basketball participants at SMA Negeri 2 Kuningan. The study applied a pre-experimental methodology that included a one group pretest-posttest design. Involving a sample of 15 male students selected through purposive sampling. The measurement instrument adopted a valid and reliable Balke test to measure VO2Max. The treatment in the form of HIIT training was implemented during a span of four weeks, consisting of three sessions weekly. Data analysis used a normality test (Shapiro-Wilk), pretest results p = 0.123 and posttest p = 0.135 (> 0.05); homogeneity test p = 0.396 (> 0.05); and paired sample t-test which showed p = 0.000 (<0.05) which indicated a significant impact of HIIT on increasing VO2Max. These findings suggest that HIIT is effective in increasing VO2Max and can be implemented as a school physical training strategy. This study contributes to the development of efficient training models, and provides a basis for future studies related to the role of nutrition, sleep quality and psychological factors on VO2Max.